The Influence of E-Service Quality, Product Quality Perception, Experiential Marketing on Repurchase Intent Through Customer Satisfaction - Rimiyati, Hasnah; Daffa, Raihan (Journal of Business and Halal Industry, 2025)
This study aims to analyze the influence of e-service quality, product quality perception, and experiential marketing on repurchase intentions through customer satisfaction among consumers of coffee in the Special Region of Yogyakarta. The subject of the study is a consumer domiciled in the Special Region of Yogyakarta, the sample was used by 168 respondents with non-probability sampling techniques and purposive sampling methods. Data collection was carried out through the distribution of questionnaires using google forms. Data analysis and hypothesis testing using AMOS Structural Equation Modeling. The results of the data analysis show that e-service quality has a positive and significant effect on customer satisfaction, product quality perception has a positive and significant effect on customer satisfaction, experiential marketing has a positive and significant effect on customer satisfaction, e-service quality has a positive and significant effect on repurchase intention, product quality perception has a positive but not significant effect on repurchase intention, e-experiential marketing has a positive and insignificant effect on repurchase intention, customer satisfaction has a positive and significant effect on repurchase intention. Furthermore, customer satisfaction is able to partially mediate the influence of e-service quality on repurchase intention, customer satisfaction is able to mediate fully the influence between product quality perception on repurchase intention, and customer satisfaction is able to mediate the full influence between experiential marketing on repurchase intention.